ASSESSMENT OF MOBILE ROBOT LOAD-CARRYING POTENTIAL VIA DC GEARBOX MOTOR TORQUE - Harsa Dhani; Redationo, Nereus Tugur; Dhancis, William (Universitas Katolik Widya Karya Malang, 2024)
The primary function of mobile robots is to transport various loads, including their own weight and additional cargo. Ensuring adequate torque in the wheel motors is crucial for effective load-bearing and movement. This study investigates the load-carrying capabilities of the TT DC gearbox motor, a popular and cost-effective choice for small robots. A mobile robot equipped with four TT DC gearbox motors and employing skid steering locomotion was constructed for this purpose. The robot featured a container designed to carry sand, and its load capacity was tested by gradually increasing the weight until the robot could no longer move. Experimental results showed that the maximum load the robot could carry on a flat surface was 4000 grams, which corresponds to 1000 grams per 5 cm diameter wheel, driven by a stall torque of 0.08336 Nm (0.85 kg.cm). This finding is consistent with the motor's specified stall torque of 0.8 kg.cm at 6V. These results suggest that the maximum load of a mobile robot can be predicted using the motor's stall torque specification and the wheel radius through the total tractive effort (TTE) formula. This study offers valuable insights into estimating the performance limits of DC gearbox motors used in driving mobile robots.